2018
DOI: 10.1007/s11033-018-4357-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-mediate transformation of echinocystic acid by whole cells of filamentous fungus Cunninghamella blakesleana CGMCC 3.910

Abstract: Structural modification of echinocystic acid (EA), a pentacyclic triterpenoid with wide spread biological activities was investigated by microbial transformation. Microbe-mediate transformation of EA was carried out by filamentous fungus Cunninghamella blakesleana CGMCC 3.910. Four metabolites 3β, 7β, 16α-trihydroxy-olean-12-en-28-oic acid (EA-2); 3β, 7β, 16β,19β-tetrahydroxy-olean-12-en-28-oic acid (EA-3); 3β, 7β, 16α, 21β-tetrahydroxy-olean-12-en-28-oic acid (EA-4); 3β, 7β, 16α-trihydroxy-olean-11, 13(18)-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As compared to traditional chemical methods, microbial transformations have greater advantages in oxidizing unactivated C–H bonds, and we can activate saturated C–H bonds of EA to expand its structural diversity and develop its pharmaceutical properties ( Xu et al, 2017 ). Some studies have found that a new method of biotransformation could provide EA derivatives with cleavage and 7-member-lactone of ring A and derivatives with single or double hydroxylations, proving that this method could overcome the shortcomings of traditional chemical modification methods ( Fu et al, 2018 ; Fu et al, 2019 ).…”
Section: Triterpenesmentioning
confidence: 99%
“…As compared to traditional chemical methods, microbial transformations have greater advantages in oxidizing unactivated C–H bonds, and we can activate saturated C–H bonds of EA to expand its structural diversity and develop its pharmaceutical properties ( Xu et al, 2017 ). Some studies have found that a new method of biotransformation could provide EA derivatives with cleavage and 7-member-lactone of ring A and derivatives with single or double hydroxylations, proving that this method could overcome the shortcomings of traditional chemical modification methods ( Fu et al, 2018 ; Fu et al, 2019 ).…”
Section: Triterpenesmentioning
confidence: 99%